The power of social commerce: TikTok's impact on Gen Z consumer purchasing behavior - Poh, Stella; Hasan, Djohan Gunawan; Sudiyono, Krist Ade (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
Consumer shopping behavior has changed from brick-and-mortar to online shopping due to the COVID-19 pandemic. The development of online shopping was accompanied by social media technology, resulting in the emergence of the social commerce phenomenon. Social commerce, as a platform that supports two activities at once, has advantages over e-commerce platforms. However, in reality, the adoption of social commerce has not been utilized effectively by business actors, and not a few MSMEs have suffered losses due to the presence of social commerce platforms. This study was conducted to understand the adoption of social commerce platforms by utilizing social media content and live streaming to influence consumer purchases using the AIDA model and TAM model theories. This study uses quantitative methods by distributing questionnaires to 246 respondents and structural equation modeling (SEM) analysis techniques. The results showed that social media content and live streaming can inform consumers clearly and interestingly about products to build consumer attention and interest, which ultimately encourages consumer purchases. This study can be implemented by business owners to optimize the application of social media content and live streaming when running a business to increase consumer attractiveness and purchases.